Targeting ROCK activity to disrupt and prime pancreatic cancer for chemotherapy - Vennin, Claire (Small GTPases, 2017)
Pancreatic ductal adenocarcinoma (PDAC) is a devastating disease; the identification of novel targets and development of effective treatment strategies are urgently needed to improve patient outcomes. Remodeling of the pancreatic stroma occurs during PDAC development, which drives disease progression and impairs responses to therapy. The actomyosin regulatory ROCK1 and ROCK2 kinases govern cell motility and contractility, and have been suggested to be potential targets for cancer therapy, particularly to reduce the metastatic spread of tumor cells. However, ROCK inhibitors are not currently used for cancer patient treatment, largely due to the overwhelming challenge faced in the development of anti-metastatic drugs, and a lack of clarity as to the cancer types most likely to benefit from ROCK inhibitor therapy. In 2 recent publications, we discovered that ROCK1 and ROCK2 expression were increased in PDAC, and that increased ROCK activity was associated with reduced survival and PDAC progression by enabling extracellular matrix (ECM) remodeling and invasive growth of pancreatic cancer cells. We also used intravital imaging to optimize ROCK inhibition using the pharmacological ROCK inhibitor fasudil (HA-1077), and demonstrated that short-term ROCK targeting, or ‘priming’, improved chemotherapy efficacy, disrupted cancer cell collective movement, and impaired metastasis. This body of work strongly indicates that the use of ROCK inhibitors in pancreatic cancer therapy as ‘priming’ agents warrants further consideration, and provides insights as to how transient mechanical manipulation, or fine-tuning the ECM, rather than chronic stromal ablation might be beneficial for improving chemotherapeutic efficacy in the treatment of this deadly disease.